Design and manufacture of three-dimensional biodegradable protective packaging buffers - Chew, Boon Hock. (2008)
The focus of the research reported herein is to compare the relative merits and limitations of a biodegradable starch-based packaging material called ECO-FOAM® to those of EPS.